Rosuvastatin ameliorates high‐fat and high‐cholesterol diet‐induced nonalcoholic steatohepatitis in rats. (7th January 2013) - Okada, Yoshihisa; Yamaguchi, Kanji; Nakajima, Tomoki; Nishikawa, Taichiroh; Jo, Masayasu; Mitsumoto, Yasuhide; Kimura, Hiroyuki; Nishimura, Takeshi; Tochiki, Nozomi; Yasui, Kohichiroh; Mitsuyoshi, Hironori; Minami, Masahito; et al.
Abstract Background/Aims Statins, which are inhibitors of 3‐hydroxy‐3‐methylglutaryl coenzyme A reductase and inhibit endogenous cholesterol synthesis, possess pleiotropic activities, such as anti‐inflammatory, anti‐oxidative and antifibrotic effects. Here, we investigated whether statins ameliorate steatohepatitis using a high‐fat and high‐cholesterol (HFHC) diet‐induced rat model. Methods Eight‐week‐old male Sprague–Dawley rats were fed control chow or HFHC diet. Half of the HFHC diet‐fed rats were orally administered 2 mg/kg/day rosuvastatin for 12 weeks. Hepatic injury, steatosis, fibrosis and markers of lipid peroxidation/oxidant stress were evaluated. Results As previously reported, HFHC diet induced steatohepatitis in rat livers with hypercholesterolaemia. Rosuvastatin decreased Oil Red O stained‐positive areas, liver/body weight ratio, serum total cholesterol levels and hepatic free fatty acid contents in HFHC diet‐fed rats. Further study revealed that rosuvastatin significantly decreased hepatic mRNA expression of tumour necrosis factor‐α and interleukin‐6, serum alanine aminotransferase levels and hepatic lobular inflammation grade. Hepatic fibrosis was also ameliorated by rosuvastatin with decreases in hepatic mRNA expression of transforming growth factor‐β, connective tissue growth factor and type‐1 procollagen. Similarly, hepatic Sirius red stained or α‐smooth muscle actin stained‐positive areas and expression of markers of lipid peroxidation/oxidant stress [hepatic 8‐hydroxy‐oxyguanosine and hepatic 4‐hydroxy‐2‐nonenal] were decreased. Interestingly, whereas the expression of carnitine palmitoyltransferase‐1 and long‐chain acyl‐CoA dehydrogenase was not affected, that of catalase and acyl‐coA oxidase was restored. Conclusions These data suggest that rosuvastatin improved not only hepatic steatosis but also hepatic injury and fibrosis via improved peroxisomal β‐oxidation in this rat HFHC model.